Lupus podocytopathy and antiphospholipid syndrome in a child with SLE: A case report and literature review - Guo-min Li; Guo-min Li; Yi-fan Li; Yi-fan Li; Qiao-qian Zeng; Qiao-qian Zeng; Xiao-mei Zhang; Xiao-mei Zhang; Hai-mei Liu; Hai-mei Liu; Jia-yan Feng; Jia-yan Feng; et al. (Frontiers Media S.A., 2022)
Lupus podocytopathy is a glomerular lesion in systemic lupus erythematosus (SLE) characterized by diffuse podocyte foot process effacement (FPE) without immune complex (IC) deposition or with only mesangial IC deposition. It is rarely seen in children with SLE. A 13-year-old girl met the 2019 European League Against Rheumatism (EULAR)/ American College of Rheumatology (ACR) Classification Criteria for SLE based on positive ANA; facial rash; thrombocytopenia; proteinuria; and positive antiphospholipid (aPL) antibodies, including lupus anticoagulant (LAC), anti-β2 glycoprotein-I antibody (anti-β2GPI), and anti-cardiolipin antibody (aCL). The renal lesion was characterized by 3+ proteinuria, a 4.2 mg/mg spot (random) urine protein to creatinine ratio, and hypoalbuminemia (26.2 g/l) at the beginning of the disease. Kidney biopsy findings displayed negative immunofluorescence (IF) for immunoglobulin A (IgA), IgM, fibrinogen (Fb), C3, and C1q, except faint IgG; a normal glomerular appearance under a light microscope; and diffuse podocyte foot process effacement (FPE) in the absence of subepithelial or subendothelial deposition by electron microscopy (EM). Histopathology of the epidermis and dermis of the pinna revealed a hyaline thrombus in small vessels. The patient met the APS classification criteria based on microvascular thrombogenesis and persistently positive aPL antibodies. She responded to a combination of glucocorticoids and immunosuppressive agents. Our study reinforces the need to consider the potential cooccurrence of LP and APS. Clinicians should be aware of the potential presence of APS in patients with a diagnosis of LP presenting with NS and positivity for aPL antibodies, especially triple aPL antibodies (LCA, anti-β2GPI, and aCL).